Anthropometric profile and associated variables of patients admitted to a pediatric intensive care unit (Research, Society and Development, 2021)
Introduction: The diagnosis of malnutrition and signs of nutritional risk, if identified, are fundamental for individualized dietary intervention in critically ill patients to ensure an improvement in nutritional status and clinical outcomes of these patients. Objective: To evaluate the anthropometric status of patients admitted to a PICU, as well as to verify its association with age, length of stay and clinical outcomes. Methods: Observational, cross-sectional and retrospective study. The sample was composed of 88 patients hospitalized from February to July 2019. Assessments of the anthropometric status of the patients were performed. Variables collected included demographic data, clinical diagnosis, length of stay, and reason for patient discharge. Analyses were performed in the SPSS version 20.0 program. Categorical variables were presented as absolute and relative frequencies, and continuous variables as medians and interquartile ranges. To evaluate the association between variables, the chi-square test was used. Results: According to the anthropometric evaluation of the patients 63.2% were eutrophic, 8.1% were overweight and 28.7% were malnourished, of these 68% were severely malnourished. There was no statistically significant association between the variables analyzed. Conclusion: Evaluation of the anthropometric status of critically ill patients admitted to the Pediatric ICU in this study showed a high percentage of malnourished children and no statistically significant association between anthropometric status, age, length of stay and the outcomes length of stay and death.